Genome assembly of the JD17 soybean provides a new reference genome for comparative genomics. Issue 4 (21st February 2022) - Yi, Xinxin; Liu, Jing; Chen, Shengcai; Wu, Hao; Liu, Min; Xu, Qing; Lei, Lingshan; Lee, Seunghee; Zhang, Bao; Kudrna, Dave; Fan, Wei; Wing, Rod A; et al.
Abstract: Cultivated soybean ( Glycine max ) is an important source for protein and oil. Many elite cultivars with different traits have been developed for different conditions. Each soybean strain has its own genetic diversity, and the availability of more high-quality soybean genomes can enhance comparative genomic analysis for identifying genetic underpinnings for its unique traits. In this study, we constructed a high-quality de novo assembly of an elite soybean cultivar Jidou 17 (JD17) with chromosome contiguity and high accuracy. We annotated 52, 840 gene models and reconstructed 74, 054 high-quality full-length transcripts. We performed a genome-wide comparative analysis based on the reference genome of JD17 with 3 published soybeans (WM82, ZH13, and W05), which identified 5 large inversions and 2 large translocations specific to JD17, 20, 984–46, 912 presence–absence variations spanning 13.1–46.9 Mb in size. A total of 1, 695, 741–3, 664, 629 SNPs and 446, 689–800, 489 Indels were identified and annotated between JD17 and them. Symbiotic nitrogen fixation genes were identified and the effects from these variants were further evaluated. It was found that the coding sequences of 9 nitrogen fixation-related genes were greatly affected. The high-quality genome assembly of JD17 can serve as a valuable reference for soybean functional genomics research.